2023
DOI: 10.3847/1538-4357/acc32c
|View full text |Cite
|
Sign up to set email alerts
|

Stellar-reddening-based Extinction Maps for Cosmological Applications

Abstract: Cosmological surveys must correct their observations for the reddening of extragalactic objects by Galactic dust. Existing dust maps, however, have been found to have spatial correlations with the large-scale structure of the Universe. Errors in extinction maps can propagate systematic biases into samples of dereddened extragalactic objects and into cosmological measurements such as correlation functions between foreground lenses and background objects and the primordial non-Gaussianity parameter f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…First, compared to most Planck-based FIR emission dust maps (e.g., Meisner & Finkbeiner 2015;Planck Collaboration et al 2016), SFD has less CIB contamination as shown in CM19. Compared to stellar reddening maps from Pan-STARRS and Gaia (e.g., Green et al 2019;Mudur et al 2023), SFD is of far higher S/N, which leads to less noise in extinction corrections. Compared to full-sky H I-based reddening maps (e.g., Lenz et al 2017), SFD has a higher angular resolution and traces dust column more directly.…”
Section: Csfd As a New Standard Dust Mapmentioning
confidence: 97%
“…First, compared to most Planck-based FIR emission dust maps (e.g., Meisner & Finkbeiner 2015;Planck Collaboration et al 2016), SFD has less CIB contamination as shown in CM19. Compared to stellar reddening maps from Pan-STARRS and Gaia (e.g., Green et al 2019;Mudur et al 2023), SFD is of far higher S/N, which leads to less noise in extinction corrections. Compared to full-sky H I-based reddening maps (e.g., Lenz et al 2017), SFD has a higher angular resolution and traces dust column more directly.…”
Section: Csfd As a New Standard Dust Mapmentioning
confidence: 97%